Milk Thistle Leaves Aqueous Extract as a New Corrosion Inhibitor for Aluminum Alloys in Alkaline Medium - Al-Rudaini , Khudhair Abbas Kareem; Al-Saadie , Khulood Abid Saleh (Iraqi Journal of Science, 2021)
The aqueous extract of milk thistle (Silybum marianum) leaves as a green corrosion inhibitor for AA7051 aluminum alloy in sodium hydroxide solution was investigated at a range of temperatures. Potentiodynamic polarization findings exhibit a mixed–type inhibitor with directly increased inhibition efficiency with the concentration of inhibitor. The adsorption of the inhibitor on aluminum alloy obeys Langmuir isotherm and the kinetic as well as thermodynamic parameters were measured and discussed.